Does knee pain in the community behave like a regional pain syndrome? Prospective cohort study of incidence and persistence. Issue 9 (17th November 2006) - Palmer, K T; Reading, I; Calnan, M; Linaker, C; Coggon, D
Abstract : Objectives: To investigate whether knee pain in the community behaves like a regional pain syndrome, determined by its association with mental health, self-rated health (SRH) and beliefs about prognosis. Methods: An 18-month postal follow-up was conducted in 1798 working-aged subjects, sampled from the community. At baseline questions were asked about pain in the knee lasting ⩾1 day in the previous 12 months, mental health (Short-Form 36), somatising tendency (elements of the Brief Symptom Inventory), SRH and concern about 12-month prognosis. At follow-up we asked about knee pain during the last 4 weeks, and whether it had been present for ⩾14 days or prescription-treated. Associations with incidence and persistence were explored using logistic regression. Results: The 1256 participants (70% response) comprised 468 with knee pain at baseline and 788 without. Among the former, 49% had persistent knee pain at follow-up, while among the latter, 15% reported new symptoms. Incident prescription-treated knee pain was strongly associated with all of the mental health variables and with SRH. The odds of knee pain persisting were significantly raised in the least versus most favourable bands of somatising tendency and SRH, and persistence was also significantly more common among those who at baseline were concerned that they would still have a problem in 12 months. Conclusions: Our observations support the hypothesis that knee pain in the community shares risk factors in common with other non-specific regional pain syndromes.